Young Learners’ Perception of Picture as Motivation Booster in English as Foreign Language - Febiyanti Liza Riani; Muhimatul Ifadah; Dodi Mulyadi (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
Young learners’ awareness of learning English in many places are still interesting to be investigated in Indonesia since in the elementary school, English sometimes taught and some other institution decided to not taught it for some reasons. The study was designed to investigate the student’s perception of picture to help them in boosting motivation in learning English as a foreign language.  In addition, they were being affirmed to elaborate their engagement in the classroom.  The phenomena were observed and questionnaire were managed to get the data. From the study it was found that student’s motivation is improving, revealed from the observation and the questionnaire’s result.  The students’ engagement in learning English was more dynamic and the classroom atmosphere become more joyful. Further, it can be interpreted that they were become more enthusiastic and stimulated when learning English. Supporting these facts, they affirmed that learning English was best experienced whenever the teacher used an interesting media, choosing a fun topic, and giving them chance to compete with their classmates.